Inflammation in neurocysticercosis: clinical relevance and impact on treatment decisions - Hamamoto Filho, Pedro T [UNESP]; Fragoso, Gladis; Sciutto, Edda; Fleury, Agnès (Taylor & Francis, 2021)
Introduction: Neurocysticercosis is caused by the localization of Taenia solium larvae in the central nervous system. The disease remains endemic in most countries of Latin America, Asia and Africa. While major improvements have been made in its diagnosis and treatment, uncertainties persist regarding the clinical implications and treatment of the inflammatory reaction associated with the disease. Areas covered: In this review, based on PubMed searches, the authors describe the characteristics of the immune-inflammatory response in patients with neurocysticercosis, its clinical implications and the treatment currently administered. The dual role of inflammation (participating in both, the death of the parasite, and the precipitation of serious complications) is discussed. New therapeutic strategies of potential interest are presented. Expert opinion: Inflammatory reaction is the main pathogenic mechanism associated to neurocysticercosis. Its management is mainly based on corticosteroids administration. This strategy had improved prognostic of patients as it allows for the control of most of the inflammatory complications. On the other side, it might be involved in the persistence of parasites in some patients, despite cysticidal treatment, due to its immunosuppressive properties. New strategies are needed to improve therapeutical management, particularly in the severest presentations.
Keywords: Anti-inflammatory drugs; corticosteroids; inflammation; neurocysticercosis; neuroinflammation; parasite; taenia solium